STUDI ANALISA PERHITUNGAN NILAI HARMONIK TEGANGAN DAN ARUS PADA BUDDHA TZU CHI HOSPITAL - Laurensius Richard Mulyadi Richard; Insani Abdi Bangsa (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2023)
ABSTRACT The occurrence of harmonics is caused by the non-linear operation of the electrical load. The level of harmonic distortion or what is called Total Harmonic Distortion (THD) in a transformer can cause losses that affect the efficiency of the transformer. In this study, THD measurements were carried out on four transformers at Tzu Chi Hospital. This research was conducted using observation, documentation, and direct measurements in the field to analyze within the limits of the IEEE 519-2014 standard. The purpose of this study was to analyze the main electrical system at Tzu Chi Hospital, analyze the value of Total Harmonic Distortion (THD) for voltage analysis. and currents at Tzu Chi Hospital. THDv based on the measurement results are transformer 1 4.8%, transformer 2 2.48%, transformer 3 1.51%, transformer 5 5%. While the THDi results obtained after measurement are transformer 1 20.2%, transformer 2 29 ,4%, transformer 3 14.78%, transformer 5 37.8%. Even after measurement, THDv was found to conform to the IEEE 519-2014 standard, and THD was found to be non-compliant with the IEEE 519-2014 standard. ABSTRAK Timbulnya harmonik disebabkan oleh operasi beban listrik non-linier. Tingkat distorsi harmonik atau yang disebut dengan Total Harmonic Distortion (THD) pada suatu trafo dapat menimbulkan rugi-rugi yang mempengaruhi efisiensi trafo. Pada penelitian ini dilakukan pengukuran THD pada empat trafo di Rumah Sakit Tzu Chi. Penelitian ini dilakukan dengan metode observasi, dokumentasi, dan pengukuran langsung di lapangan untuk menganalisis kesesuaian dengan batasan standar IEEE 519 2014. Tujuan dari penelitian ini adalah untuk menganalisis sistem kelistrikan utama di Rumah Sakit Tzu Chi, menganalisa perhitungan nilai Total Harmonic Distortion (THD) untuk tegangan dan arus di Rumah Sakit Tzu Chi. THDv berdasarkan hasil pengukuran yaitu transformator 1 4,8%, transformator 2 2,48%, transformator 3 1,51%, transformator 5 5%.sedangkan THDi hasil yang didapat setelah dilakukan pengukuran adalah transformator 1 20,2%, transformator 2 29,4%, transformator 3 14,78%, transformator 5 37,8%. Bahkan setelah pengukuran, THDv diketahui sesuai dengan standar IEEE 519 2014, dan THDi diketahui tidak sesuai dengan standar IEEE 519 2014.